Credibility assessment of cold adaptive Pseudomonas jesenni MP1 and P. palleroniana N26 on growth, rhizosphere dynamics, nutrient status, and yield of the kidney bean cultivated in Indian Central Himalaya - Khan, Amir; Singh, Ajay Veer; Pareek, Navneet; Arya, Pratima; Upadhayay, Viabhav Kumar; Kumar Jugran, Arun; Kumar Mishra, Pankaj; Goel, Reeta (Frontiers in Plant Science, 2023)
Kidney bean productivity and nutritional quality are declining due to less nutrient accessibility, poor soil health, and indigent agronomic practices in hilly regions, leading to the distressed native microflora, a fall in farmer's income, and malnutrition in consumers. Concerning such issues, the present investigation was designed to assess the impact of Pseudomonas jesenii MP1 and Pseudomonas palleroniana N26 treatment on soil health, microbial shift, yield and nutrient status of kidney bean in Indian central Himalayan, i.e., Harsil and Chakrata. P. jesenii MP1 and P. palleroniana N26 were characterized as cold adaptive PGPR as they possessed remarkable In vitro plant growth promoting traits. Further, field trial study with PGPR treatments demonstrated remarkable and prolific influence of both isolates on yield, kidney bean nutrient status, and soil health at both geographical locations. As they have exceptionally improved grain yield (11.61-23.78%), protein (6.13-24.46%) and zinc content (21.86-61.17%) over control. The metagenomic study revealed that bioinoculants inoculation also concentrated the nutrient mobilizing and plant beneficial microorganisms in the vicinity of kidney bean rhizosphere. Moreover, correlation analysis also confirmed that the plant growth promoting traits of P. jesenii MP1 and P. palleroniana N26 are the basis for improved yield and nutrient status of kidney bean. Further, cluster and principal component analysis revealed that P. jesenii MP1 and P. palleroniana N26 both exhibited prominent influence on yield attributes of kidney bean at both the locations. Above results revealed that these bioinoculants are efficient plant growth promoter and nutrient mobilizer, hence in order to take step forward towards the sustainable agriculture, they could be used as green technology to augment human health and farmer's income by improving soil health, yield, and nutrient status of kidney bean at hilly regions.